Evaluating the Performance of an Arduino-Based Strain Sensor System in a Cantilever Beam using Plastic Ruler Under Load Conditions - Amran, Nur Amirah; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2025)
Strain measurements are important for assessing the structuralintegrity of engineering systems, especially in detecting potentialfailures and planning maintenance strategies. Traditional strainmeasurement methods, however, are frequently costly and complicated,which restricts their use in small-scale and educational settings. Thisstudy focuses on the development and evaluation of an Arduino-basedstrain sensor system for cantilever beam testing using a plastic ruler asa test sample. The system integrates a strain gauge module, an LCD forreal-time data display, and a buzzer and LED to provide feedback basedon preset thresholds. The performance of the system was evaluatedunder various load conditions to determine its reliability and accuracyin measuring strain. Experimental results show a strong correlationwith theoretical predictions, confirming the potential of the system forpractical applications in structural health monitoring. This low-cost anduser-friendly approach provides an effective tool for educationalpurposes, enabling direct exploration of strain distribution and bendingmechanics.